Interrupting tumor necrosis factor–alpha signaling prevents parenteral nutrition–associated cholestasis in mice. Issue 5 (18th November 2021) - El Kasmi, Karim C.; Anderson, Aimee L.; Devereaux, Michael W.; Balasubramaniyan, Natarajan; Suchy, Frederick J.; Orlicky, David J.; Shearn, Colin T.; Sokol, Ronald J.
Abstract: Background: We have recently reported a mouse model of PN‐associated cholestasis (PNAC) in which combining intestinal inflammation and PN infusion results in cholestasis, hepatic macrophage activation, and transcriptional suppression of canalicular bile acid, bilirubin and sterol transporters Abcb11, Abcc2 and Abcg5/8 . The aim of this study was to examine the role of TNFα in promoting PNAC in mice. Methods: First, recombinant TNFα was administered to mice as well as in hepatocyte cell culture. Second, Tnfr1/2 KO or wild‐type (WT) mice were exposed to dextran sulfate sodium (DSS) for 4 days followed by soy‐oil lipid emulsion–based PN infusion through a central venous catheter for 14 days (DSS‐PN). Finally, WT/DSS‐PN mice were also infused with infliximab at 10 mg/kg on days 3 and 10 of PN. PNAC was defined by increased serum aspartate aminotransferase, alanine aminotransferase, total bile acids, and bilirubin. Results: Intraperitoneal injection of TNFα into WT mice or TNFα treatment of Huh7 hepatocarcinoma cells and primary mouse hepatocytes suppressed messenger RNA (mRNA) transcription of bile ( Abcb11, Abcc2 ]) and sterol transporters ( Abcg5 /8) and their regulators Nr1h3 and Nr1h4 . DSS‐PN mice with PNAC had increased hepatic TNF α mRNA expression and significant reduction of mRNA expression of Abcb11, Abcc2, Abcg5/8, Nr1h3, and Nr1h4 . In contrast, PNAC development was prevented and mRNA expression normalized in both Tnfr1/2 KO /DSS‐PN mice and DSS‐PN mice treated with infliximab. Conclusions: TNFα is a key mediator in the pathogenesis of PNAC through suppression of hepatocyte Abcb11, Abcc2, and Abcg5/8 . Pharmacologic targeting of TNFα as a therapeutic strategy for PNAC thus deserves further investigation.